Motivation and Learning Outcomes: Correlation in physical education learning - Indriani, Khafifah; Ashfaq, Muhammad (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The purpose of this study was to determine the relationship between motivation and learning outcomes of class VII2 students of SMP Negeri 4 Pekanbaru. This research was conducted using a type of correlational research, namely research that calculates the level of the relationship between a variable and other variables. The population in this study were 35 students of class VII2 SMP Negeri 4 Pekanbaru. The sample in this study was a total population of 35 people. The instrument in this study was a motivation questionnaire test and a report card in physical education. The correlation analysis technique used is the product moment correlation. Based on the results of the research that has been done, it can be concluded that there is a relationship between motivation and learning outcomes of physical education for class VII2 students of SMP Negeri 4 Pekanbaru. Recommendations for other researchers in the future, in order to be able to study more broadly in improving student physical education learning outcomes and using a large enough sample.